Dust properties in the circumstellar environment of carbon stars. Issue Volume 14:Issue S343(2019) (August 2018) - Mečina, M.; Aringer, B.; Brunner, M.; Kerschbaum, F.; Groenewegen, M. A. T.; Nowotny, W.
Abstract: Herschel PACS imaging observations of carbon stars show well-resolved spherically symmetric detached shells around several objects. In the case of U Hya the shell is additionally detected in scattered visible light and in the far UV. The remarkable spherical symmetry justifies a straightforward application of 1D models to constrain the properties of the dust envelope, whose modulation in density is a consequence of short epochs of highly increased mass loss and/or wind-wind interaction between outflows of different velocity. We perform dust radiative transfer calculations, first based on a parametrised density distribution, and in a more sophisticated approach on a combination of stationary wind models. The impact of dust properties, particularly grain geometry, on the results is highlighted.